Hubungan Antara Indeks Massa Tubuh Dan Lemak Visceral Dengan Hipertensi Pada Mahasiswa Universitas ’Aisyiyah Yogyakarta - Muhammad Raffa Januarsyah; Siti Fadhilatun Nashriyah; Dewi Rizzky Mutiarasari (Borneo Nursing Journal (BNJ), 2026)
Background: Hypertension is known as a silent killer because in most sufferers it does not cause symptoms, so it often goes unnoticed until complications in target organs occur. Hypertension not only occurs in the elderly but is also commonly found in young people. College students are a group included in the young adult category. In this age group, hypertension can have an impact not only related to physical health conditions, but also on cognitive function and academic activities. Body mass index and visceral fat are factors that play a role in increasing the risk of hypertension. Research Objective: This study aims to analyze the relationship between body mass index and visceral fat with hypertension in students at 'Aisyiyah University Yogyakarta. Research Method: This study is a quantitative study with an observational analytical design using a cross-sectional approach. The study sample consisted of 97 active students selected using a purposive sampling technique. Measurements of body mass index and visceral fat were carried out using Bioelectrical Impedance Analysis (BIA), while blood pressure was measured using a digital sphygmomanometer. In addition, height measurements were used to calculate body mass index using a stadiometer. Data analysis used the Chi-Square test for eligible variables and Fisher's Exact Test for variables that did not meet the Chi-Square test requirements. Research Result: The results showed that most respondents had a body mass index in the non-overweight category (65%), normal visceral fat category (84%), and did not experience hypertension (80%). The proportion of hypertension was higher in respondents with the overweight category (41%), as well as in respondents with high visceral fat (69%). The results of the analysis showed a significant relationship between body mass index and hypertension (p =